Research in Library Classification - Neelameghan, A.; Gopinath, M. A. (Journal of Information and Knowledge, 2002)
An essential basis for research in library classification is the study of the structure and developmerit of the universe of subjects. A Classification based on a resilient design methodology, and a holistic approach would ensurea good foundation for the document retrieval system. The Indian System of Thought in Classification has taken the five Laws of Library Science as the basic guiding principles, deduced canons and principles for classification, enunciated helpful postulates, and demonstrated classification work as belonging to three planes. It has attempted to grasp the essence of the relation among the constituents of the universe of subjects at the near-seminal level, progressively applied objective scientific method to classification, and developed a precise terminology for the subject. The advantages of the above lines of approach are illustrated and the kind of research involved in the different developments are mentioned. A set of problems for pursuit is given.